Analysis of the influence of some factors on the temperature distribution and tire durability - Vu Hai Quan; Tran Quang Tam; Nguyen Trong Duc; Le Hong Quan; Tran Phuc Hoa; Kirill Evgenievich Karpukhin (Researcher and Lecturer Society, 2026)
Increasing vehicle operating speeds place greater thermal and mechanical demands on automotive tires, making the assessment of tire behavior under varying speed conditions essential for safety and durability. This study investigates the effects of speed, load, and inflation pressure on the temperature distribution and durability of the Bridgestone ECOPIA EP150 tire using numerical simulation in Ansys Workbench. The results indicate that the shoulder region exhibits the highest temperature, which rises with increasing vehicle speed. Inflation pressure and vertical load significantly influence the contact area and stress distribution. An inflation pressure of 34 psi is identified as optimal, limiting localized heat generation and maintaining tire durability under realistic operating conditions. The findings provide practical guidance for tire selection and usage, particularly in tropical climates, and support improved safety and operational efficiency. Furthermore, the simulation-based approach demonstrates the effectiveness of numerical analysis as a predictive tool for evaluating tire performance under complex operating conditions, reducing reliance on extensive experimental testing.